'This Is Who I Am'. Issue 1 (1st April 2022) - Hartwig, Kalvin; Turin, Mark
This dialogue between Anishinaabe scholar and filmmaker, Kalvin Hartwig, and board member Mark Turin explores Indigenous identity, language revitalization, reclamation and resurgence and the pernicious legacy of settler colonialism.